Transient buildup and dissipation of a compressed plasma shockwave in arc-discharge plasma beams. (23rd December 2021) - Zhang, Zhe; Fu, Yifeng; Zhang, Zun; Lin, Xin; Qi, Jiayun; Ling, William Yeong Liang; Tang, Haibin; Herdrich, Georg
Abstract: Electric propulsion offers the advantage of a high specific impulse through a large exhaust velocity and has seen significant progress in space flight applications. Recently, we observed a transient plasma shockwave during pulsed plasma thruster operation when the plasma beam impacted a probe surface. However, details regarding the plasma shockwave formation are still unknown. This work is an experimental investigation of the compression-induced plasma shockwave in the presence of a planar obstruction. To study the complete shockwave buildup and dissipation process, an ultra-high-speed imaging system was set up to visualize the time-resolved shockwave morphology at a sub-microsecond level. In addition, the local magnetic field and plasma density were measured using 2D magnetic coils and a triple Langmuir probe, respectively. The successive images of the shockwave give us a comprehensive understanding of the shockwave buildup process. During the 12 μ s operational period of the thruster, two shockwaves were formed during the first cycle of the discharge. It is also interesting to note that there is a 1 μ s dissipation period between the two shockwaves with the same cloud of plasma compressing against the probe surface. A shockwave model is also developed to predict the appearance of the two shockwaves. The implication is that the local magnetic field strength can be a key indicator for the plasma shockwave buildup and dissipation process.